Pengembangan Sistem Panduan Mobile Dengan Audio dan Teks Berdasarkan Augmented Reality (Android) Untuk Pengunjung di Museum Bali - Gerson Feoh; Christina Purnama Yanti (AITI, 2018)
The Bali museum is one of the museums in which objects of artistic, cultural and historical of Balinese against the invaders are kept. However, there are still few visitors coming to the museum. One way to increase a number of visitors is by using a technology in the form of interactive application for them. This research made visitors of Bali museum as subjects /user studies, while the designed application was aimed at knowing the users’ responses toward it. Previously, a study of mobile-based AR had been conducted to see the needs of the users. A guide in the form of text and sound were also added. Augmented Reality is a technology that combines virtual world and the real world simultaneously. AR technology requires a camera to capture the picture of marker whichwill display the 3D object from one of the Bali museum’s collections. The 3D object was created with software marker of 3D objects. In this study, both software blender and software unity were used to develop 3D object and the application of AR. The application runs on in 5 inch – screen Android devices and provide information in the form of Indonesian text and audio bilingual, both in Indonesian and English.